Peran Kepemimpinan Pendidikan dalam Menumbuhkan Entrepreneur Koperasi Sekolah - Isnaeni Asifatul Khasnah; Lyra Nabila Putri; Zuhda Ruchama Khoiruna; Siswadi Siswadi (LP3M IAI Al Urwatul Wutsqo Jombang, 2026)
This study aims to analyze the role of educational leadership in optimizing school cooperatives as a medium for entrepreneurship learning. The research employs a qualitative approach using a library research method by synthesizing relevant scientific literature published over the last ten years. The analysis is conducted descriptively and analytically by integrating findings related to cooperative management, student engagement, and educational leadership. The results indicate that school cooperatives play a strategic role in fostering students’ entrepreneurial spirit, particularly when managed systematically through planning, organizing, implementing, and controlling functions. Furthermore, active student participation in cooperative activities enhances independence, creativity, responsibility, and risk-taking through an experiential learning approach. Participatory and transformational educational leadership is also crucial in creating a conducive learning environment and optimizing the educational function of school cooperatives. The contribution of this study lies in strengthening the conceptual framework that integrates cooperative management, student engagement, and educational leadership as a unified system in entrepreneurship education. However, this study is limited by the absence of empirical field data. Therefore, further research using empirical approaches is recommended to obtain more comprehensive findings.